The Role of TikTok in Shaping Teenagers' Opinions on Social Issues - Aisyah Nurjanah (PT Publikasiku Academic Solution, 2025)
TikTok, as a short-video social media platform, has emerged as a central interactive space for teenagers to understand and shape their opinions on social issues. This study aims to explore how TikTok content influences adolescent perspectives on topics such as mental health, climate change, gender equality, and bullying. Using a descriptive qualitative approach, data were collected through in-depth interviews and participatory observation of content creators who consistently address social topics. The findings reveal that teenagers undergo a five-stage interaction process: discovering content, watching, engaging, seeking more information, and forming personal opinions. TikTok facilitates active teen involvement in social discourse through emotionally driven and narrative-based content. The study suggests that educators, policymakers, and social organizations can effectively utilize TikTok as an educational medium, although limitations exist regarding the geographic scope and duration of the research.